PENCAPAIAN STANDAR INDONESIAN SUSTAINABLE PALM OIL (ISPO) DALAM PENGELOLAAN PERKEBUNAN KELAPA SAWIT DI KALIMANTAN TIMUR / Achievement of Indonesian Sustainable Palm Oil Standards of Palm Oil Plantation Management in East Borneo Indonesia - Rusli Anwar; Santun RP Sitorus; Anas Miftah Fauzi; nFN Widiatmaka; nFN Machfud (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
Strong opinions have been expressed toward oil palm plantation industry in Indonesia, and these opinions portray that oil palm plantation development in Indonesia has caused the destruction of the environment. One of the efforts currently undertaken by the Indonesian government to ensure the sustainability of the palm oil industry is establishing sustainability standard called the Indonesian Sustainable Palm Oil (ISPO) which is mandatory. ISPO is